Radiometric illumination for short-range radar (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2016)
The usage of methods and devices of close multichannel location requires usage of illumination devices to increase radio brightness of the research’s object. As a source of radiation apart of traditional noise oscillators, gas-charge tubes can be used, which are not used for regular location. During usage of the gas-charge tubes, the noise power level should be taken into consideration as well as the radiation’s polarization particular qualities, which are dependent on tube’s construction. The gas-charge tubes have sufficient and stable level of СПМШ in millimeter wave length despite the fact that gas-charge radiation in optical range has narrow peaks. LED diodes have considerable brightness in optical range, however, they do not possess noise radiation in millimeter wave length. The research of different sources of noise radiation in MW frequency range with aim of increase in radio brigtness contrast of objects and its usage as an illumination in multichannel radiometric systems is represented. Low-noise modulation of energy-efficient lamps allows to use them in designing of the modular radiometric systems in MW frequency range for remote detection of objects. Power flux density of the noise pannel is lower than the one which is produced by energy-efficient lamps, yet radiation front of electromagnetic wave is almost flat at the distance of 300-400 mm from the panel.